Юсупов лирикасында мақтымқулы дәстүрлери - Ҳайтбаева, В. И (FAN va JAMIYAT, 2025)
The article studies the poetic traditions of Makhtumkuli in the didactic-philosophical direction in the poetry of I.Yusupov. It is proved that the poems included in the series "On the Path of Makhtumkuli" by I.Yusupov are in harmony with Makhtumkuli's poems in terms of formal, ideological-thematic and genre-stylistic features, and that his